2000
DOI: 10.1093/bioinformatics/16.12.1120
|View full text |Cite
|
Sign up to set email alerts
|

A knowledge model for analysis and simulation of regulatory networks

Abstract: We introduce an ontological model for the representation of biological knowledge related to regulatory networks in vertebrates. We outline a taxonomy of the concepts, define their 'whole-to-part' relationships, describe the properties of major concepts, and outline a set of the most important axioms. The ontology is partially realized in a computer system designed to aid researchers in biology and medicine in visualizing and editing a representation of a signal transduction system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…For example, AVAD automatically classified co-localize and synergize as interaction verbs, both of which do not appear in the detailed knowledge model for interaction verbs constructed for the GeneWays system [16]. Our analysis showed that AVAD proposes a large number of verbs that humans did not include in the knowledge base and that most of these verbs should in fact be included in the knowledge base.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, AVAD automatically classified co-localize and synergize as interaction verbs, both of which do not appear in the detailed knowledge model for interaction verbs constructed for the GeneWays system [16]. Our analysis showed that AVAD proposes a large number of verbs that humans did not include in the knowledge base and that most of these verbs should in fact be included in the knowledge base.…”
Section: Resultsmentioning
confidence: 95%
“…In addition to the validation, database management and visualization components, its text analysis component includes algorithms for the detection and disambiguation of genes and proteins in text and for the detection of relationships that match patterns known to the system. Currently, the patterns that represent the system's understanding of biological relationships are encoded as part of GeneWays detailed knowledge model, which was built by hand by consulting experts in the domain of pathway analysis [16]. These patterns are then represented as rules in a semantic grammar and a parser adapted to the biological domain [17], extracts new instances of gene and protein relationships as new texts arrive.…”
Section: Comparison With a Manually Built List Of Activation Verbsmentioning
confidence: 99%
“…processing (NLP) techniques can help to extract useful semantics from scientific papers [6], [7], [8], even the best NLP methods still do not perform well in terms of precision and recall of scientific papers [9], [10].…”
Section: Using Semantics For More Accurate Searchingmentioning
confidence: 99%
“…Although many protein and nucleotide databases still use mainly human readable text as annotation, different approaches have been developed to structure this knowledge. These were as straightforward as defining specific keywords or as complicated as setting up an ontology for different aspects of protein function [Rzhetsky et al, 2000]; probably, the most widely used of the latter approaches is from the Gene Ontology project [Consortium, 2008].…”
Section: Introductionmentioning
confidence: 99%